Apostle of persuasion : theology and rhetoric in the Pauline letters - Thompson, James W. (James Weldon), 1942- (Grand Rapids, MI, Baker Academic, 2020)
This book is the culmination of a career of researching and teaching Paul's letters. Highly respected senior New Testament scholar James Thompson offers a unique approach to Pauline theology, focusing on Paul's attempts to persuade his audience toward moral formation. Thompson recognizes Paul as a pastor who brought together theology and rhetoric to encourage spiritual formation in his communities. Attempts to find total consistency in Paul's writings fail, says Thompson, because Paul's persuasive tactics changed depending on the situation he was addressing.
Introduction: Rhetoric and theology in Paul -- The rhetoric of Paul's letters -- Paul and the Pharisaic tradition -- Where Christian theology began : Jesus and the early church -- Paul's ethos and his theology -- First Thessalonians : a template for theological reflection -- Christology and persuasion -- Greco-Roman values and the theology of the cross : the Corinthian correspondence -- The theology of the cross and justification by faith -- Romans, the righteousness of God, and the defense of Paul's ministry -- 'Seek the things that are above' : persuasion in Colossians and Ephesians -- Pauline theology and rhetoric in the Pastoral Epistles -- Conclusion: Paul's pastoral theology
Includes bibliographical references and indexes.
Keywords: Bible. -- Theology